Relationship Between Mother's Knowledge Of Breast Milk Companion Food With Accuracy of Breastfeeding Companion Feeding - Ayu Andhira; Tenriwati; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Background: Breast milk companion food should be given after the baby is 6 months old because it can provide great benefits to the baby (Alam, 2010). Factors that play an important role to prevent improper feeding of breast milk are maternal knowledge factors and maternal work factors. Maternal behavior in this case plays an important role to prevent improper feeding of breast milk so that it will reduce the risk of the baby experiencing indigestion and can have stronger endurance. There are some mothers who provide breast milk companion food is not on time. Research objectives: To Find Out the Relationship Between Maternal Knowledge Levels About Breast Milk Companion Foods With Timeliness of Breastfeeding Companion Feeding in the Working Area of Puskesmas Caile Bulukumba Regency. Method: This type of research is quantitative research using a non-experimental design using the Cross-Sectional approach. A sample of 49 respondents was taken by the consecutive sampling method. The data analysis in this study used a chi-square test statistical test. Results: Based on the results of univariate analysis, it is known that the mother's knowledge of MP-BREAST MILK feeding is at most sufficient and good categories as many as 44 people (67.7%). And the timeliness of giving MP-BREAST MILK is the most appropriate category as many as 38 people (58.5%). The results of the analysis using the chi-square test obtained a significant value of 0.001 (p < 0.05). Conclusion: There is a relationship between the level of maternal knowledge about breast milk companion food and the timeliness of breastfeeding companion feeding in the working area of the public health caile bulukumba district. And it is recommended for hospital institutions are expected to consider applying as a nursing relationship between the level of maternal knowledge about breast milk companion food with the timeliness of breastfeeding companion feeding